Laminated Sheet

The laminated sheet with alternating layers of optimized 3d transition element content and orientation addresses the challenge of shielding high-frequency electromagnetic waves, offering superior electromagnetic shielding and moldability.

JP7665929B2Active Publication Date: 2025-04-22TORAY INDUSTRIES INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020127089
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-28
Publication Date
2025-04-22
Estimated Expiration
2040-07-28

AI Technical Summary

Technical Problem

Existing electromagnetic wave shielding materials struggle to effectively shield high-frequency electromagnetic waves due to limitations in permeability and moldability, particularly in applications requiring thin, flexible, and uniformly thick sheets.

Method used

A laminated sheet is developed with five or more layers of alternating A and B layers, where at least one layer contains 0.5% to 90% particles with 1% to 100% by mass of 3d transition elements, optimizing the content and orientation of these particles to enhance electromagnetic shielding and moldability.

Benefits of technology

The laminated sheet achieves high electromagnetic wave shielding properties, including transmission attenuation and return loss, while maintaining excellent moldability and film formation capabilities, even at high frequencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665929000006
    Figure 0007665929000006
  • Figure 0007665929000007
    Figure 0007665929000007
  • Figure 0007665929000008
    Figure 0007665929000008
Patent Text Reader

Abstract

To provide a laminated sheet having excellent electromagnetic wave shielding, molding, and film forming properties.SOLUTION: A laminated sheet includes a unit having A layers and B layers alternately laminated, with the total number of A and B layers being five or more. At least one of the A and B layers contains particles (particles X) of 0.5 vol.% or more and 90 vol.% or less, which include 3d transition elements of 1 mass% or more and 100 mass% or less. The content of the particles X in the B layers is higher than that in the A layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate sheet having excellent electromagnetic wave shielding properties. [Background technology]

[0002] With the advancement of communication technology, electromagnetic waves of various frequency bands are used and fly around in the atmosphere, such as meter waves in the hundreds of MHz to several GHz bands, which are mainly used for mobile phones and wireless communication, centimeter waves in the several GHz to several tens of GHz bands, which are mainly used for mobile communications such as 4G and 5G and wireless LAN (Wi-fi) communications, and millimeter waves in the several tens of GHz to several hundreds of GHz bands, which are mainly used for automobile collision prevention radar. Electromagnetic waves of appropriate frequency bands are selected according to the amount of information, the distance to be transmitted, and the purpose, but since electromagnetic waves of similar frequency bands are used in various devices and applications, there is an increasing need for electromagnetic wave shielding materials that block electromagnetic waves to prevent device malfunctions, communication failures, information leaks, and effects on the human body, which is sensitive to electromagnetic waves. In particular, in recent years, the development of communication technologies that use electromagnetic waves in the GHz frequency band has accelerated in order to realize high-speed and large-capacity communication, and electromagnetic wave shielding materials that can block electromagnetic waves in that frequency band are required.

[0003] Electromagnetic waves are waves that are composed of two components, an electric field and a magnetic field, which propagate through space while vibrating against each other. Electromagnetic shielding materials that block electromagnetic waves are materials that reflect electromagnetic waves on the surface or inside the material, or absorb electromagnetic waves inside the material, thereby causing loss and attenuation of electromagnetic wave energy, and the effect can be enhanced by combining reflection and absorption. For example, the effect of surface reflection of electromagnetic waves can be enhanced by the difference in electrical resistance (impedance) between the air interface and the electromagnetic shielding material interface, and generally, electromagnetic shielding properties over a wide range of frequency bands can be achieved by coating and laminating a material with a very low resistance value, such as metal (e.g., copper), on the surface of a substrate (Patent Document 1).

[0004] On the other hand, electromagnetic wave shielding by absorption involves the inclusion of conductive and / or magnetic materials in the substrate, which absorbs the electromagnetic waves that enter the substrate as induced currents, thereby causing the loss of electromagnetic wave energy, and this absorption performance is achieved by including carbon materials, ferrite, and metal materials containing various 3d transition elements such as iron in dielectric polymers such as rubber (Patent Documents 2 to 4). In addition, by overlapping layers with different impedances, electromagnetic waves can be multiple-reflected inside the electromagnetic wave shielding material, causing interference between the reflected electromagnetic waves and offsetting and loss due to the internal electromagnetic wave absorbing material (Patent Document 5).

[0005] In particular, the electromagnetic wave shielding effect due to absorption varies depending on the dielectric (insulating) substrate, the formulation (type, combination, content) of the conductive material contained therein, the thickness of the substrate, etc., but the arrangement state of the conductive material within the substrate is also an important factor. For example, there is a finding called the Maxwell-Wagner effect, which shows that the effect of the entire shielding material can be increased by arranging conductive materials in a certain direction and stacking them side by side to improve conductivity (Non-Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2011-502285 [Patent Document 2] JP 2012-94764 A [Patent Document 3] JP 2000-243615 A [Patent Document 4] JP 2004-39703 A [Patent Document 5] JP 2018-56492 A [Non-patent literature]

[0007] [Non-Patent Document 1] ZMDang,Prog.Matter.Sci.,2012,57,660-723 [Non-Patent Document 2] Eikichi Yoshida, Journal of the Magnetic Society of Japan, 2002, vol.26, 893 Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the electromagnetic shielding material using reflection as in Patent Document 1, metal sputtering, vacuum deposition, coating with a paste containing a conductive material or a magnetic material, and other techniques are used, but these techniques can cause short circuits in electronic devices and communication devices due to peeling of the coated layer, and problems can arise in terms of durability. On the other hand, the electromagnetic shielding material using absorption as in Patent Documents 2 and 3 can be divided into two types based on the form of use, and the evaluation of the effect can also be divided into two ways. One is a method in which the electromagnetic shielding material is used alone as shown in Figure 1, and the effect is evaluated by how much the electromagnetic shielding material 3 can shield the incident electromagnetic wave 1, in other words, the amount of transmitted electromagnetic wave 2 reduced by the electromagnetic shielding material 3 (transmission attenuation amount) (Equation (1)). The other is a method in which the electromagnetic shielding material is attached to a material that can reflect electromagnetic waves (electromagnetic wave reflection layer) as shown in Figure 2. More specifically, the reflected electromagnetic wave 5 when an incident electromagnetic wave 1 is irradiated onto an electromagnetic wave shielding material 3 with an electromagnetic wave reflecting layer 4 attached thereto is compared with the reflected electromagnetic wave 5 when the incident electromagnetic wave 1 is irradiated onto the electromagnetic wave reflecting layer 4 alone, and the amount of reflected electromagnetic wave 5 reduced by the electromagnetic wave shielding material 3 (reflection attenuation) is calculated to evaluate the effectiveness (Equation (2)). However, most of these technologies can only absorb low-frequency electromagnetic waves, mainly below 1 GHz. This is due to the decrease in magnetic permeability at high frequencies, which is a characteristic of magnetic materials (Sneak's limit).

[0009]

number

[0010]

number

[0011] In the formula (1), T is the transmission attenuation, E i is the electric field strength of the incident electromagnetic wave, E t represents the electric field strength of the transmitted electromagnetic wave. In equation (2), A represents the return loss, and E r1 is the electric field strength of the electromagnetic wave reflected when there is an electromagnetic wave shielding material, and E r2 represents the electric field strength of the electromagnetic waves reflected when there is no electromagnetic wave shielding material.

[0012] Therefore, in order to absorb electromagnetic waves in the high frequency band above 1 GHz, it has been necessary to make the electromagnetic shielding material thicker, orient the magnetic material (Patent Document 4), or use a magnetic material with a special crystal structure (Patent Document 5).However, when the thickness of the electromagnetic shielding material is increased, the stiffness of the electromagnetic shielding material increases, making it difficult to apply the material to applications requiring formability, such as wrapping it around a cable or combining it with a housing having a complex uneven shape.

[0013] In addition, one method of orienting magnetic bodies to improve electromagnetic wave absorption performance is to orient flat magnetic bodies using shear flow during sheet molding, but if the electromagnetic wave shielding material is made thicker to improve absorption performance, the magnetic bodies are not sufficiently oriented and the absorption performance decreases. In other words, there is a so-called trade-off between the orientation of the magnetic bodies and the thickness of the electromagnetic wave shielding material, and it was difficult to achieve both and improve absorption performance with this method.

[0014] Another method is to use magnetic materials with special crystal structures (such as epsilon iron oxide) to improve the absorption performance in the high frequency band, but such magnetic materials themselves are very expensive and difficult to apply to a wide range of applications. Furthermore, considering the moldability and production efficiency of electromagnetic shielding materials, continuous sheeting by melt extrusion using thermoplastic resin is preferable to press-processed products using thermoplastic resin, but when molding a single-layer sheet with a high concentration of magnetic material, the change in melt viscosity of the resin during extrusion (thixotropy) becomes strong, which causes uneven discharge during extrusion molding into a sheet, making it difficult to form a sheet of uniform thickness, and the electromagnetic shielding material becomes brittle and prone to cracking.

[0015] An object of the present invention is to solve these problems and to provide a laminate sheet that is excellent in electromagnetic shielding properties, moldability, and film-forming properties. [Means for solving the problem]

[0016] In order to solve the above problems, the present invention has the following configuration: A laminate sheet including a unit in which five or more A layers and B layers are alternately laminated, at least one of the A layers and the B layers contains 0.5% by volume to 90% by volume of particles (particles X) containing 1% by mass to 100% by mass of a 3d transition element, and the B layers contain more particles X than the A layers. Effect of the Invention

[0017] The present invention provides a laminated sheet having a configuration in which layers having different contents of particle X are alternately laminated, whereby the particle X can be highly aligned and dispersed to achieve high electromagnetic wave shielding properties (transmission attenuation), and which also has excellent moldability and film-forming properties. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a schematic diagram showing a method for measuring the transmission attenuation. [Diagram 2] FIG. 4 is a schematic diagram showing a method for measuring return loss. [Diagram 3] FIG. 2 is a schematic diagram showing the half-width and electromagnetic wave attenuation of the return loss peak having the largest peak-top attenuation among the peaks obtained by measuring the return loss peaks of a laminate sheet. [Figure 4] 2 is a schematic diagram showing the half-value width and electromagnetic wave attenuation of the return loss peak with the largest peak-top attenuation among the peaks obtained by measuring the return loss peaks of a laminate sheet of an embodiment different from that of FIG. 1. [Diagram 5] FIG. 3 is a schematic diagram showing the half-width and electromagnetic wave attenuation of the return loss peak with the largest peak-top attenuation among the peaks obtained by measuring the return loss peaks of a laminate sheet of an embodiment different from those of FIGS. 1 and 2. [Figure 6] FIG. 4 is a schematic diagram showing the half-width and electromagnetic wave attenuation of the return loss peak with the largest peak-top attenuation among the peaks obtained by measuring the return loss peaks of a laminate sheet of an embodiment different from those of FIGS. 1 to 3. [Figure 7] FIG. 2 is a schematic diagram illustrating polarization. [Figure 8] FIG. 1 is a schematic diagram illustrating linear polarization. [Figure 9] FIG. 1 is a schematic diagram illustrating circularly polarized waves. [Figure 10] FIG. 1 is a schematic diagram illustrating elliptically polarized waves. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The laminate sheet of the present invention is described in detail below. The laminate sheet of the present invention includes a unit in which A layers and B layers are alternately laminated in five or more layers, and at least one of the A layers and the B layers contains 0.5% by volume to 90% by volume of particles (particles X) containing 1% by mass to 100% by mass of a 3d transition element, and the B layer contains more particles X than the A layer.

[0020] The laminated sheet of the present invention is required to contain particles (particles X) containing 1% by mass or more and 100% by mass or less of 3d transition elements. Particles X refer to particles in which 1% by mass or more and 100% by mass or less of 3d transition elements account for 100% by mass of all elements constituting the particles. Examples of 3d transition elements include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, and zinc. Among them, particles X preferably contain iron, cobalt, or nickel, which are likely to exhibit ferromagnetism, and more preferably contain iron.

[0021] As the particles X, in addition to the above-mentioned 3d transition elements themselves, metal oxides, metal nitrides, metal carbides, metal borides, metal oxide nitrides, metal hydroxides, metal oxide borides, organometallic complexes, alloys, etc. containing any of these can be used. Among them, organometallic complexes are preferable from the viewpoint of maintaining performance in the high frequency band, and for example, carbonyl iron, hexacyano iron, phosphine iron, amino iron, and derivatives thereof can be suitably used. The particles X may contain only one type of 3d transition element, or may contain multiple types of 3d transition elements. In addition, when multiple types of 3d transition elements are contained, if the total amount of the 3d transition elements is 1% by mass or more and 100% by mass or less when all elements constituting the particles are 100% by mass, the particles are considered to correspond to the particles X.

[0022] It is important that at least one of the layer A and layer B of the laminate sheet of the present invention contains particles X in an amount of 0.5 volume % to 90 volume %, and that the layer B contains more particles X than the layer A. Here, "containing particles X in an amount of 0.5 volume % to 90 volume %" means that the layer contains particles that satisfy the above requirements for particles X in an amount of 0.5 volume % to 90 volume % when all components constituting the layer are taken as 100 volume %. In addition, "layer B contains more particles X than layer A" means that the content (volume %) of particles X in layer B calculated on the basis that all components constituting layer B are 100 volume % is greater than the content (volume %) of particles X in layer A calculated on the basis that all components constituting layer A are 100 volume %.

[0023] The following three embodiments are examples of the embodiment in which "at least one of the A layer and the B layer contains particles X at 0.5 volume % or more and 90 volume % or less, and the B layer contains more particles X than the A layer." The first embodiment is an embodiment in which the amount of particles X in the A layer is 0 volume % or more and less than 0.5 volume %, and the amount of particles X in the B layer is 0.5 volume % or more and 90 volume % or less. The second embodiment is an embodiment in which the amount of particles X in the A layer and the amount of particles X in the B layer are both 0.5 volume % or more and 90 volume % or less, and the amount of particles X in the B layer is greater than the amount of particles X in the A layer in terms of volume. The third embodiment is an embodiment in which the amount of particles X in the A layer is 0.5 volume % or more and 90 volume % or less, and the amount of particles X in the B layer exceeds 90 volume %. By adopting such an embodiment, the A layer or the B layer contains a sufficient amount of particles X, and the magnetic properties (transmission attenuation) of the two layers are different, so that electromagnetic wave reflection at the layer interface can be realized. Among these, from the viewpoint of suppressing layer disturbances and deterioration of film-forming properties and processability caused by an excess of the particles X, the first and second embodiments are preferred.

[0024] If the content of particle X in both layers A and B exceeds 90% by mass, the lamination may be disturbed and the film-forming stability and processability may be impaired. In addition, the difference in the content of particle X between layers A and B is also small, so that the magnetic properties of both layers tend to be similar, and the electromagnetic shielding properties are also inferior. On the other hand, if the content of particle X in both layers A and B is less than 0.5% by volume, the electromagnetic shielding properties may not be sufficient due to a lack of particle X. From the viewpoint of achieving both the electromagnetic shielding properties of the laminated sheet and the film-forming stability and processability, the content of particle X in layer B is preferably 2% by volume or more and 50% by volume or less, more preferably 3% by volume or more and 30% by volume or less, and even more preferably 5% by volume or more and 20% by volume or less, when the total components constituting the layer are taken as 100% by volume.

[0025] In the laminate sheet of the present invention, when particles X are contained in both the A layer and the B layer, in order to provide the laminate sheet with electromagnetic wave shielding properties, it is required that the amount (volume %) of 3d transition elements in the A layer and the amount (volume %) of 3d transition elements in the B layer are not equal. If the amount (volume %) of 3d transition elements in the A layer and the amount (volume %) of 3d transition elements in the B layer are equal, the magnetic properties of the A layer and the B layer tend to be equal unless resins with significantly different magnetic properties are used in the A layer and the B layer, so that reflection of electromagnetic waves at the layer interface cannot be obtained, and the electromagnetic wave shielding properties (transmission attenuation) of the laminate sheet are reduced. The amount of 3d transition elements in each layer can be adjusted, for example, by adjusting the amount of particles X or the amount of 3d transition elements in the particles X.

[0026] Examples of a method for evaluating whether or not a particle contained in each layer corresponds to particle X include a method in which, after peeling off each layer, the particles are extracted with a solvent suitable for dissolving components other than the particles, and the composition is evaluated by a known elemental analysis method or the like, and a method in which a cross section of a laminated sheet is analyzed using a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) or a transmission electron microscope-energy dispersive X-ray spectroscopy (TEM-EDX).

[0027] It is important that the laminated sheet of the present invention includes a unit in which five or more layers of A and B are alternately laminated. Here, "a unit in which five or more layers of A and B are alternately laminated" refers to a structure in which A and B layers are alternately and continuously present in a total of five or more layers. That is, it refers to a state in which resins are laminated according to a regular arrangement of A(BA)n or B(AB)n (n is a natural number of 2 or more). A laminated sheet having a unit in which five or more layers of A and B are alternately laminated (hereinafter, sometimes simply referred to as an "alternate laminate unit of A and B layers") is considered to be "including a unit in which five or more layers of A and B are alternately laminated" regardless of the presence or absence of layers other than A and B layers. As long as the laminated sheet of the present invention has an alternating laminate unit of A and B layers, the outermost layer may be any of A layers, B layers, and layers other than A and B layers, and the outermost layers on both sides may be the same layer or different layers, but from the viewpoint of realizing the concept of the laminated sheet of the present invention in which electromagnetic wave shielding properties are enhanced by receiving resistance from particles X in the inner layer, it is preferable that A layers are the outermost layers on both sides. The laminate sheet may have one or more alternate laminate units of A layer and B layer.

[0028] As a means for obtaining a laminated sheet having an alternating laminate unit of A layer and B layer, as described later, a method of laminating layers having different compositions by stepwise pressure bonding, or a method of laminating them all at once using a lamination device can be used. In addition, a functional layer different from the alternating laminate unit, such as another electromagnetic wave reflection layer or electromagnetic wave absorption layer, may be formed on the alternating laminate unit of A layer and B layer. In the case of an embodiment having a plurality of alternating laminate units of A layer and B layer, the plurality of laminate units can be laminated via an adhesive layer or directly by thermocompression bonding. In the case of an embodiment having a plurality of alternating laminate units of A layer and B layer, alternating laminate units having peak tops of return loss peaks in different frequency bands may be laminated together to be used as a material that simultaneously shields desired plurality of frequency bands.

[0029] The laminated sheet of the present invention has an alternating laminate unit of layers A and B, which can improve the electromagnetic shielding properties targeting a specific frequency band while suppressing the thickness of the entire laminated sheet. Usually, in order to improve the electromagnetic shielding properties targeting a specific frequency band, it is necessary to improve the relative permeability of the entire sheet. In addition, in a conventional single-film sheet, it is necessary to add a high concentration of magnetic material (particles X) or increase the thickness of the sheet in order to reduce the permeability in the high frequency band due to the Sneak limit. In contrast, when the laminated sheet has an alternating laminate unit of layers A and B, the particles X can be tightly confined in each layer, and the particles X can be oriented to maintain a high permeability even in the high frequency band. The effect of orientation is particularly noticeable when flat particles X are used. In addition, by making the permeabilities of layers A and B different values, electromagnetic waves are reflected due to impedance mismatch at the layer interface, so that the electromagnetic shielding properties (transmission attenuation) can be improved.

[0030] In order to improve the electromagnetic shielding properties of the laminated sheet, it is also preferable to adjust the relative permittivity in addition to the relative permeability, and a method of adding a conductive material (particle Y) can be used to adjust the relative permittivity. In that case, by forming an alternating laminate unit of A layer and B layer with different content of particle Y, dielectric polarization occurs at the interface of layers with different relative permittivities, making it easier for current to pass inside the sheet, and improving the electromagnetic shielding properties. In addition, by being able to densely confine the particle Y within each layer, the conductivity within the layer is increased, and the layer is more susceptible to loss due to the resistance of the particle Y added inside, and a higher electromagnetic shielding properties can be achieved than conventional products. As a result, a laminated sheet with excellent electromagnetic shielding properties (reflection loss, transmission loss) can be obtained even if the sheet is thin.

[0031] The number of layers in the alternating laminate unit of A layer and B layer contained in the laminate sheet is preferably 13 layers in total or more, more preferably 31 layers in total or more, and even more preferably 101 layers in total, since the more the layer interfaces between the layers showing high relative magnetic permeability and relative dielectric constant and the layers showing low relative magnetic permeability and relative dielectric constant, the easier it is to obtain electromagnetic wave shielding properties. The upper limit of the number of layers is preferably 1001 layers in terms of production cost, film formability, and electromagnetic wave shielding performance. By setting the number of layers in the laminate unit of A layer and B layer to 1001 layers or less, the increase in production cost due to the enlargement of the equipment such as a feed block having fine slits can be suppressed. At the same time, depending on the dispersion state, shape, and size of the particles X and Y, the number of layers increases and the thickness of each layer becomes thin, which causes a problem of layer thickness disorder due to the manifestation of thixotropy, and the electromagnetic wave shielding properties and the steepness of the electromagnetic wave frequency band to be shielded can be maintained.

[0032] The laminated sheet of the present invention preferably has at least one return loss peak in the frequency band of 1 MHz to 100 GHz, and more preferably has at least one return loss peak in the frequency band of 1 GHz to 100 GHz. Specifically, whether or not the laminated sheet has at least one return loss peak in the frequency band of 1 MHz to 100 GHz can be evaluated by the following procedure. First, using a coaxial waveguide method or a free space method, an electromagnetic wave is irradiated onto a laminated sheet combined with a metal reflector plate made of aluminum or the like on the back side, and the intensity of the electromagnetic wave reflected by the metal plate and traveled back and forth within the laminated sheet is measured to calculate the return loss in each frequency band. Next, a return loss spectrum is drawn in which the vertical axis represents return loss and the horizontal axis represents frequency in the frequency band of 1 MHz to 100 GHz, and it is confirmed whether or not a return loss peak exists therein. Details of the measurement method are shown in the section "(2) Transmission loss, return loss".

[0033] In the laminated sheet of the present invention, when the return loss peak having the largest return loss at the peak top in the frequency band of 1 MHz to 100 GHz is defined as return loss peak 1, the return loss at return loss peak 1 is preferably 5 dB or more and 150 dB or less. Here, the peak top usually refers to the position where the slope of the tangent of the return loss spectrum inverts from positive to negative or from negative to positive. The radio wave attenuation at the return loss peak refers to the return loss at the peak top compared to the baseline. The return loss peak 1 can be determined from a chart in the frequency band of 1 MHz to 100 GHz with the return loss on the vertical axis and the frequency on the horizontal axis. By making the laminated sheet have a return loss peak within the above range, the laminated sheet can be applied to various products such as high-frequency communication compatible devices and millimeter wave radar.

[0034] 3 to 6, which are schematic diagrams showing the half-width and electromagnetic wave attenuation of the return loss peak with the largest peak-top attenuation among the peaks obtained by measuring the return loss peaks of a laminated sheet, will be used to explain the return loss peak at the peak top. In Figs. 3 to 6, reference numeral 6 denotes the baseline, reference numeral 7 denotes return loss peak 1, reference numeral 8 denotes the peak top of return loss peak 1, reference numeral 9 denotes the return loss I at the peak top, and reference numeral 10 denotes the half-width R of return loss peak 1.

[0035] In the case where a single peak top is present as shown in FIG. 3, the return loss I at the return loss peak 1 can be expressed as the difference in the reflection amount between the peak top and the baseline at the frequency at which the peak top is located, with the baseline of the peak as the reference. In some cases, the baseline is inclined as shown in FIG. 4. In such cases, the peak top is determined as the position where the value obtained by subtracting the slope of the baseline from the slope of the return loss spectrum changes from positive to negative, or from negative to positive. Even if the return loss of the baseline is high as shown in FIG. 5, if the peak has a unique peak top, the difference in the return loss between the baseline and the peak top of the peak can be determined as the return loss at the peak top. In the case where a spectrum having multiple peak tops including a shoulder peak is obtained as shown in FIG. 6, the return loss I at the frequency of the highest peak among the multiple peak tops is expressed as the difference between the return loss corresponding to the peak top and the return loss of the baseline of the entire peak including the multiple peak tops.

[0036] The return loss of the radio wave attenuation of the return loss peak 1 is preferably 5 dB or more. The return loss of less than 5 dB means that the transmittance of the electromagnetic wave is higher than 30%, that is, the electromagnetic wave shielding property is insufficient. From the viewpoint of realizing sufficient electromagnetic wave shielding property, the return loss of the return loss peak with the largest return loss in the laminated sheet of the present invention is preferably 15 dB or more, more preferably 20 dB or more, and even more preferably 30 dB or more. On the other hand, the return loss of the return loss peak with the largest peak top attenuation of about 30 dB indicates that 99.9% of the incident electromagnetic wave is shielded compared to the electromagnetic wave shielding property of the frequency band around the peak, and means that it has very high electromagnetic wave shielding property. From the viewpoint of the electromagnetic wave shielding property of the laminated sheet, the upper limit of the return loss of the return loss peak with the largest peak top attenuation is not particularly limited, but from the viewpoint of feasibility, it is 150 dB, more preferably 100 dB.

[0037] In addition, the frequency bandwidth in which the return loss peak with the largest peak top return loss is 5 dB or more and 150 dB or less is preferably 1 GHz or more and 20 GHz or less in terms of steep and high electromagnetic wave shielding properties and reducing the influence of frequency band fluctuations due to thickness unevenness. This narrow bandwidth makes it possible to sharply cut electromagnetic waves in the target band. On the other hand, this wide bandwidth reduces the influence on the cutoff properties of the target frequency even if the frequency band to be cut varies due to the thickness unevenness of the laminated sheet. From the above viewpoint, specifically, the frequency bandwidth in which the return loss peak 1 has a return loss of 5 dB or more is more preferably 3.0 GHz or more and 20.0 GHz or less, and even more preferably 5.0 GHz or more and 20.0 GHz or less.

[0038] The laminate sheet of the present invention is intended to obtain a high return loss by controlling the thickness and content of particles X as described above, and the design method thereof will be described in detail below. A resin containing particles X exhibits a specific relative dielectric constant and relative permeability depending on the amount of particles X added and the state of dispersion.

[0039] The frequency of the return loss peak 1 can be easily adjusted mainly by changing the thickness of the B layer and / or the A layer, but the return loss at that frequency is affected by the values ​​of the relative dielectric constant and the relative permeability. More specifically, by first making the B layer thicker (thinner), the frequency showing the return loss peak can often be lowered (raised) more effectively than by changing the thickness of the A layer. This is because the B layer contains more particles X and therefore often has a higher permeability than the A layer. However, if only one of the layers is made extremely thick or thin, this may lead to a decrease in the electromagnetic wave shielding properties due to layer disorder, so it is preferable to adjust the thicknesses of the A layer and the B layer simultaneously.

[0040] In order to increase the relative dielectric constant, it is preferable to add a conductive material (particles Y, details of which will be described later). Since the particles Y do not have much effect on the relative magnetic permeability, adding them makes it possible to independently control the relative dielectric constant, making it easy to adjust the relative dielectric constant. This is therefore preferable because it makes it easy to achieve both thinning and improved electromagnetic shielding properties. In addition, by laminating and extruding a layer to which particles Y have been added, the dispersibility of the particles Y is also improved, and in some cases, an improvement in the relative dielectric constant can be obtained.

[0041] Methods for increasing the relative magnetic permeability include adding particles X and increasing the amount of particles X. However, when particles X are added, the relative dielectric constant may also increase (deviation from the design value), so it is preferable to first increase the relative magnetic permeability with particles X and then adjust the relative dielectric constant with particles Y. In particular, when particles X having a flat shape are used, the dispersibility of particles X is improved by laminating and extruding a layer to which particles X are added, and the particles are oriented in the sheet surface direction, which may result in an improvement in the magnetic permeability.

[0042] The relative permeability can be changed by adjusting the composition and / or content of particle X, but the dielectric constant also changes accordingly, making it difficult to find the optimal content. As a result of intensive research, the inventors have found that the relative permeability can be adjusted without significantly changing the dielectric constant by setting the value obtained by multiplying the longitudinal relative permeability at return loss peak 1 by the concentration (volume %) of particle X in layer B and the value obtained by multiplying the widthwise relative permeability at return loss peak 1 by the concentration (volume %) of particle X in layer B to 0.5 or more and 1000 or less. The longitudinal direction (MD) refers to the direction in which the film runs in the manufacturing process (the winding direction of the film in the case of a film roll), and the width direction (TD) refers to the direction perpendicular to the longitudinal direction in the film plane. In the following, the value obtained by multiplying the longitudinal relative permeability at return loss peak 1 by the concentration (volume %) of particles X in layer B and the value obtained by multiplying the widthwise relative permeability at return loss peak 1 by the concentration (volume %) of particles X in layer B may be referred to as MD volume permeability and TD volume permeability, respectively. Also, both MD volume permeability and TD volume permeability may be collectively referred to as volume permeability in both directions.

[0043] By setting the volume permeability in both directions to 0.5 or more, a sufficient return loss due to the particles X can be achieved, and by setting the volume permeability in both directions to 1000 or less, errors due to changes in the relative dielectric constant caused by contact between the particles X can be suppressed, making it easier to design the laminated sheet. From the above viewpoints, the volume permeability in both directions is more preferably 5 or more and 800 or less.

[0044] In the laminated sheet of the present invention, when the real part and the imaginary part of the dielectric constant in the longitudinal direction at the return loss peak 1 are MDε' and MDε'' respectively, and the real part and the imaginary part of the dielectric constant in the width direction at the return loss peak 1 are TDε' and TDε'' respectively, it is preferable that MDε' / MDε'' and TDε' / TDε'' are both 1 or more and 1000 or less. The dielectric constant also changes depending on the amount of particle X added, but MDε' / MDε'' and TDε' / TDε'' can also be adjusted by adding a conductive material to layer A and / or layer B, or by changing the type and composition of particle X or resin. Each ε' mainly affects the reflection of electromagnetic waves at the interface, and each ε'' affects the phase shift and attenuation of electromagnetic waves inside the layer. From the viewpoint of the electromagnetic wave shielding property of the laminated sheet, it is preferable that MDε' / MDε'' and TDε' / TDε'' are both 1 or more. Furthermore, in the high ε' region, the applicable frequency shifts to the low frequency side, so in order to design a thickness capable of shielding high frequency electromagnetic waves, the film must be extremely thin, making it difficult to control variations in electromagnetic shielding properties due to layer disturbance. Therefore, it is preferable that MDε' / MDε'' and TDε' / TDε'' are both 1000 or less. From the viewpoint of achieving both the electromagnetic shielding properties of the laminate sheet and reducing layer disturbance, it is more preferable that MDε' / MDε'' and TDε' / TDε'' are both 1.5 or more and 100 or less.

[0045] In the laminated sheet of the present invention, it is preferable from the viewpoint of improving the electromagnetic wave shielding property that each particle X is oriented in the plane direction due to the positional regulation of the particles X by lamination. Therefore, it is preferable that the thickness of at least one layer containing the particles X is 1 nm or more and 30 μm or less, and it is more preferable that the thickness of all layers containing the particles X is 1 nm or more and 30 μm or less. When the thickness of the layer containing the particles X is 1 nm or more, the layer disturbance caused by the particles X breaking through the layer is reduced, and the electromagnetic wave shielding property can be maintained at a high level. On the other hand, when the thickness of the layer containing the particles X is 30 μm or less, the fluctuation of the position and orientation of the particles X in the layer is suppressed, and the effect of the positional regulation is fully exerted. The thickness of each layer can be measured by the length measurement function of a microscope using a sample image cut out from a cross section.

[0046] The thickness of the layer containing the particles X is preferably 1.1 to 10 times the average diameter of the particles X contained therein (if the particles are present as a higher-order structure, the average diameter of the entire higher-order structure). By setting the thickness of each layer within this range, the particles can be effectively oriented. Here, the average diameter of the particles X means the number-based arithmetic mean length diameter described in JIS Z8819-2 (2001). More specifically, it refers to the value obtained by observing the primary particles or higher-order structure using a scanning electron microscope (SEM), a transmission electron microscope, etc., taking the diameter of the circumscribed circle as the particle diameter, and calculating the number-based average value. In the case of a laminated film, the number-average particle diameter can be obtained by observing the surface or cross section.

[0047] From the viewpoint of suppressing the surface reflection of electromagnetic waves and increasing the reflection attenuation amount, it is preferable that the relative permittivity and / or the magnetic permeability gradually increase from the surface layer to the inner layer in the laminated sheet of the present invention. As one of the means for realizing such an aspect, it can be mentioned that the thickness of the B layer continuously increases from at least one of the surface layers to the layer at the center of the sheet. Here, "the thickness of the B layer continuously increases from the surface layer to the layer at the center of the sheet" means that in the section from the surface layer to the layer at the center of the sheet, the thickness of the B layer increases by at least one step or more, and the thickness of the B layer does not turn to decrease in the same section. When there is a layer that strongly reflects electromagnetic waves on the surface layer, the electromagnetic waves may not reach the inner layer of the laminated sheet, and the electromagnetic wave shielding property based on the concept of the laminated sheet of the present invention that enhances the electromagnetic wave shielding property by receiving the resistance of the particles X in the inner layer may not be obtained. Therefore, for example, when the A layer is the surface layer, by making the thickness of the B layer thinner closer to the surface layer, the relative magnetic permeability and relative permittivity of the surface layer can be lowered, the relative magnetic permeability / relative permittivity difference at the layer interface can be reduced, and the reflection in the portion close to the surface layer can be suppressed to improve the reflection attenuation amount. As a means for adopting such a laminated structure, for example, a method of using a feed block in which the slit width is adjusted so that the thickness of the B layer continuously increases from the surface layer toward the center can be mentioned.

[0048] From the viewpoint of enhancing the electromagnetic wave shielding property (transmission attenuation amount), it is also preferable that the laminated sheet of the present invention has a layer with a low ε' inside. That is, when the relative permittivity in the longitudinal direction in an arbitrary layer (α layer) located in the middle is MDE(α), the relative permittivity in the longitudinal direction in the layer adjacent to the α layer is MDE(α - 1) and MDE(α + 1), the relative permittivity in the width direction in the α layer is TDE(α), and the relative permittivity in the width direction in the layer adjacent to the α layer is TDE(α - 1) and TDE(α + 1), it is preferable that either one of the locations where MDE(α) < MDE(α - 1) and MDE(α) < MDE(α + 1), and the locations where TDE(α) < TDE(α - 1) and TDE(α) < TDE(α + 1) exists, and it is more preferable that both exist.

[0049] Here, the "arbitrary layer (α layer) located in the middle" refers to any layer selected from both outermost layers and layers other than the layers adjacent to them. To explain with specific examples, for instance, in a laminated sheet with a two-kind five-layer structure of layer configuration A layer / B layer / A layer / B layer / A layer, the central A layer is the "arbitrary layer (α layer) located in the middle". Also, in a laminated sheet with a two-kind 101-layer structure of layer configuration A layer / B layer / A layer / B layer ··· / A layer, the A layer or B layer from the third layer to the 99th layer can be the "arbitrary layer (α layer) located in the middle".

[0050] Moreover, "where either one of the cases where MDE(α) < MDE(α - 1) and MDE(α) < MDE(α + 1), and TDE(α) < TDE(α - 1) and TDE(α) < TDE(α + 1) exists" means that when selecting the α layer from all the layers that can be the α layer and obtaining MDE(α), MDE(α - 1), MDE(α + 1), TDE(α), TDE(α - 1), and TDE(α + 1), these values satisfy at least one of "MDE(α) < MDE(α - 1) and MDE(α) < MDE(α + 1)" and "TDE(α) < TDE(α - 1) and TDE(α) < TDE(α + 1)". To explain with specific examples, for instance, in a laminated sheet with a two-kind five-layer structure of layer configuration A layer / B layer / A layer / B layer / A layer, it means that when taking the central A layer as the α layer, the above requirements are satisfied. Also, in a laminated sheet with a two-kind 101-layer structure of layer configuration A layer / B layer / A layer / B layer ··· / A layer, it means that when taking any of the A layer or B layer from the third layer to the 99th layer as the α layer, there exists at least one layer α that satisfies the above requirements. Examples of such a method include, for example, a method of creating a difference in the amount of particle X between the α layer and the layers on both sides of it.

[0051] Where MDE(α) < MDE(α - 1) and MDE(α) < MDE(α + 1), or where TDE(α) < TDE(α - 1) and TDE(α) < TDE(α + 1), the existence of a location that satisfies the condition that either one of them exists means that there is a location where the value of at least one of ε’ in the longitudinal direction and the width direction is smaller than that of the two adjacent layers on both sides. As described above, it is preferable to suppress the reflection of electromagnetic waves in the portion close to the surface layer of the laminated sheet from the viewpoint of increasing the reflection attenuation amount of the laminated sheet. However, from the viewpoint of improving the transmission attenuation amount, it is preferable to maximize the electromagnetic wave reflection at each layer interface. Therefore, in particular, in the inner layer, it is preferable that the ε’ of adjacent layers is significantly different, and it is preferable that there is a layer where ε’ is smaller than the two adjacent layers on both sides.

[0052] It is preferable from the viewpoint of showing polarization absorption characteristics that the relative permeability of the laminated sheet of the present invention exhibits uniaxial anisotropy. Here, "the relative permeability exhibits uniaxial anisotropy" means that when the relative permeability of the laminated sheet is measured by linearly polarized waves such as the free space method or the rectangular waveguide method using a network analyzer, the relative permeability in an arbitrary direction and the relative permeability in the direction orthogonal to the said direction show different values. Also, as shown in FIG. 7, a polarized wave refers to an electromagnetic wave in which the electric field or magnetic field (precisely, the electric field vector or magnetic field vector) in the plane perpendicular to the traveling direction travels while vibrating regularly in time and space. In FIG. 7, reference numeral 11 represents the vibration direction of the electric field vector (only a part is shown), reference numeral 12 represents the traveling direction of the electromagnetic wave, reference numeral 13 represents the projection plane, and reference numeral 14 represents the locus drawn by the tip of the vibrating electric field vector (reference numerals 13 and 14 are the same in FIGS. 8 to 10 described later). The locus drawn by the tip of the vibrating electric field vector when the polarized wave is applied to an arbitrary plane drawn in space is various as described below.

[0053] Polarized waves are classified into linearly polarized waves (orthogonal polarization, parallel polarization, FIG. 8), circularly polarized waves (right-hand circular polarization, left-hand circular polarization, FIG. 9), and elliptically polarized waves (FIG. 10) according to the movement of the locus drawn by the apex of the vibration of the electric field vector when projected onto a plane perpendicular to the traveling direction of the electromagnetic wave. There is no particular limitation on the method for achieving uniaxial anisotropy of the relative permeability of the laminated sheet, but there is, for example, a method of orienting needle-shaped, elliptical, or fibrous particles by shear force or stretching during melt extrusion. In particular, such an embodiment is preferable because the particles are kneaded into a low-viscosity resin and laminated with a high-viscosity resin, whereby the orientation of the particles is promoted by the shear force received from the high-viscosity resin.

[0054] By forming a laminate sheet with uniaxial anisotropy in relative permeability, it becomes possible to exhibit high electromagnetic shielding properties only when the vibration direction of the electric field vector coincides with the direction of high relative permeability, particularly for linearly polarized waves. A laminate sheet with such properties can be preferably used for electromagnetic shielding purposes in devices that detect targets or communicate using polarized waves, such as radar and communication devices.

[0055] As described above, it is important to adjust the dielectric constant of the laminate sheet of the present invention from the viewpoint of improving the electromagnetic wave shielding property. The method of changing the dielectric constant is not particularly limited, but can be achieved, for example, by using a resin exhibiting a high dielectric constant or by incorporating particles Y, which will be described later, into a resin with high insulating properties. Since the particles Y have excellent electrical conductivity, they function as a conductive material in the laminate sheet.

[0056] The particle Y refers to a particle containing at least one element selected from C, Ag, and Au at 10% by mass or more and 100% by mass or less, and containing less than 1% by mass of a 3d transition element. If the content of the 3d transition element in the particle Y is 1% by mass or more, it may be difficult to independently adjust the relative permeability and the relative dielectric constant for designing the laminated sheet. More specifically, since the electromagnetic shielding design of the laminated sheet is performed according to formula (3) and formula (4), if the relative permeability and the relative dielectric constant cannot be independently adjusted, it may be difficult to design to shield electromagnetic waves in a desired frequency band, or the variation in the electromagnetic shielding property may be large. In the laminated sheet of the present invention, at least one of the A layer and the B layer preferably contains the particle Y at 0.5% by volume or more and 90% by volume or less. If at least one of the A layer and the B layer contains the particle Y at 0.5% by volume or more, it becomes easy to improve the relative dielectric constant to such an extent that it affects the electromagnetic shielding property. When at least one of the layers A and B contains 90% by volume or less of the particles Y, it is possible to reduce the difficulty in forming the laminate sheet.

[0057]

number

[0058]

number

[0059] In formula (3), A represents the return loss, and Z represents the impedance. In formula (4), Z represents the impedance, μ represents the magnetic permeability, ε represents the dielectric constant, i represents the imaginary unit, f represents the frequency, and d represents the layer thickness.

[0060] Examples of particles Y include conductive metals such as gold and silver, compounds thereof, and organic carbon. In particular, organic carbons having a small primary particle size and suitable for melt extrusion are preferred. Examples of organic carbons that can be used include carbon blacks (spherical carbons) such as acetylene black, channel black, lamp black, thermal black, ketjen black, and furnace black; carbon nanotubes, which are cylindrical carbons such as single-walled nanotubes, multi-walled nanotubes, and cup-stacked nanotubes; flat carbons such as graphite, graphite, and graphene; and other types of spherical graphite, cylindrical graphite, carbon microcoils, fullerenes, and carbon fibers (long fibers and short fibers). Among these, in order to utilize the effect of orientation and dispersion of the conductive material in the surface direction due to the laminated structure and to improve the conductivity of the layer containing the conductive material, it is preferable to use conductive carbon black, which is likely to develop a primary structure (linear structure). In order to form a stronger conductive path in the layer direction, it is also preferable to use, in addition to carbon black, whose structure develops in any direction, carbon nanotubes or flat carbon, which have a uniform structure and a high aspect ratio. By using organic carbon, which is easy to develop a structure, in combination with organic carbon, which has a fixed structure, the frequency band shielded by the laminated sheet can be easily changed by adjusting the ratio of the two conductive materials.

[0061] In the laminate sheet of the present invention, from the viewpoint of improving the electromagnetic wave shielding property, when the volume resistance of the laminate sheet is Ω, the logarithm of Ω to the base 10 (logΩ) is preferably 2 to 16. The volume resistance affects the electromagnetic wave shielding property of the laminate sheet, and the larger the logΩ, the easier it is for electromagnetic waves to enter the laminate sheet, and the layers inside the laminate sheet also effectively contribute to improving the electromagnetic wave shielding property. On the other hand, if logΩ exceeds 16, the electromagnetic wave will almost completely pass through the laminate sheet, and the electromagnetic wave shielding effect itself may become insufficient. From the above viewpoint, logΩ is more preferably 3 to 15, and even more preferably 4 to 14.

[0062] Methods for adjusting log Ω to 2 or more and 16 or less, or to the above-mentioned preferred range, include, for example, adding / increasing the amount of conductive material (particle Y) (increase in log Ω), applying a conductive coating (increase in log Ω), laminating with a highly insulating resin (decrease in log Ω), etc. In particular, the method of adjusting by adjusting the amount of particle Y added and laminating with a highly insulating resin is preferred from the viewpoint of simplicity.

[0063] In the laminated sheet of the present invention, from the viewpoint of achieving both reduction in unevenness in electromagnetic shielding properties and thinning, the average particle diameter of the particles X is preferably 0.01 μm or more and 10 μm or less. By having the average particle diameter of the particles X of 0.01 μm or more, aggregation is suppressed, so that the particles X are easily dispersed uniformly, and the variation in electromagnetic shielding properties is reduced. On the other hand, by having the average particle diameter of the particles X of 10 μm or less, the occurrence of lamination disorder can be suppressed without excessively increasing the thickness of each layer, so that thinning can be easily achieved, and as a result, the moldability of the laminated sheet is improved. In addition, by having the average particle diameter of the particles X of 10 μm or less, void formation by the particles X in the stretching and molding processes can be suppressed, so that the decrease in relative permeability and relative dielectric constant due to voids can also be suppressed. Furthermore, as described later, in order to increase the relative permeability in the high frequency band, the average particle diameter of the particles X is preferably 10 μm or less.

[0064] The average particle size here means the number-based arithmetic mean length diameter as described in JIS Z8819-2 (2001). More specifically, it refers to a value obtained by observing primary particles or higher-order structures using a scanning electron microscope (SEM), a transmission electron microscope, etc., taking the diameter of the circumscribed circle as the particle diameter, and calculating the number-based average value. The particles in the laminated sheet can be measured by observing the surface or cross section.

[0065] In the laminated sheet of the present invention, from the viewpoint of easily achieving the uniaxial anisotropy of the relative magnetic permeability described above, it is preferable that the ratio of the long axis to the short axis of the particle X is 1.5 or more. From the same viewpoint, it is also preferable that, after satisfying the above requirements, when the cross section of the particle X is cut along a plane perpendicular to the long axis and including the short axis and surrounded by a rectangle with a minimum area, the ratio of the short side to the long side of the rectangle is 0.5 to 1 or less. The ratio of the long axis to the short axis of the particle X being 1.5 or more means that the particle has an elongated shape. Furthermore, when the cross section of the particle X is cut along a plane perpendicular to the long axis and including the short axis and surrounded by a rectangle with a minimum area, the ratio of the short side to the long side of the rectangle being 0.5 to 1 or less means that the particle has a flat shape. Examples of the shape of the particle X that satisfies these two requirements include an elongated and flat shape, such as an elliptical disk or an elliptical cylinder.

[0066] By using such particles X, it is easy to achieve the uniaxial anisotropy of the relative magnetic permeability described above, and by combining it with a laminated structure, a suitable orientation state (positional control of particles) can be easily achieved, and the electromagnetic shielding properties in the high frequency band are also improved. In general, magnetic materials generate eddy currents in the high frequency band, so that the relative magnetic permeability decreases above a certain frequency band (Sneak's limit), but if the particles X are flat and have an average particle size of 10 μm or less, the generation of eddy currents can be suppressed, and it is possible to maintain a high relative magnetic permeability even in the high frequency band (Non-Patent Document 2).

[0067] In order to obtain the desired electromagnetic wave shielding properties, the laminate sheet of the present invention can be bonded to other laminate sheets of the same type or to laminate sheets of different thicknesses or compositions via an adhesive sheet, a pressure sensitive adhesive sheet, a double-sided tape, etc. There is no particular upper limit to the thickness, but from the viewpoints of ease of handling and thinning of the finally obtained laminate sheet, a thickness of 100 μm is preferable.

[0068] It is also preferable that the laminated sheet of the present invention has an adhesive layer having a thickness of 1 μm or more and 10 mm or less on at least one surface. By adopting such an embodiment, it becomes easy to attach it to an irradiated object such as an electromagnetic wave sensor, and it is possible to prevent electromagnetic waves in a frequency band corresponding to noise from reaching the irradiated object. As a result, the laminated sheet of the present invention functions as an electromagnetic wave shield, and adverse effects such as malfunction caused by electromagnetic waves in a frequency band corresponding to noise can be eliminated. In this case, the thickness of the adhesive layer is 1 μm or more, which makes it easy to attach the laminated sheet to the irradiated object. In addition, in the case of an application requiring return loss, it is also preferable to design the laminated sheet by taking into consideration the thickness of the adhesive layer at the design stage from the viewpoint of adjusting the frequency of the return loss peak. In that case, it is preferable to set the thickness of the adhesive layer to 1 μm or more so that the adhesive layer can absorb some unevenness on the attachment surface. By setting the thickness of the adhesive layer to 10 mm or less, it is possible to suppress deterioration of moldability due to an increase in the thickness of the laminated sheet.

[0069] Next, the electromagnetic wave-related product of the present invention will be specifically described. The electromagnetic wave-related product of the present invention is formed by mounting the laminated sheet of the present invention on any of electrical products, communication devices, and transportation facilities. As a preferred embodiment of the present invention, the laminated sheet or the electromagnetic wave shield of the above-mentioned electrical products and communication devices can be mentioned for the purpose of preventing false images caused by electromagnetic waves used in 4G / 5G communication, wireless LAN, collision prevention (ITS) radar, etc., reducing unnecessary electromagnetic wave radiation from electronic devices, semiconductors, and circuits installed inside the housing of computers, mobile phones, radios, measuring devices, medical devices, vehicle bumpers, etc., and preventing malfunction of devices due to radiation from external or adjacent devices. In addition, the laminated sheet of the present invention can be mounted on any electrical products or communication devices that use frequencies in the GHz band, and is not limited to the above.

[0070] Further, preferred embodiments of the present invention include vehicles, aircraft, ships, and other means of transportation having the laminated sheet of the present invention, walls of structures such as buildings, tunnels, guardrails, highways, bridges, and steel towers, and communication facilities such as telegraph and telephone facilities. The laminated sheet of the present invention can be applied by attaching it to structures such as floors, ceilings, walls, windows, and pillars directly via an adhesive or via other sheets, shielding plates, panels, etc. In addition, it can also be used as a wall material or window material for a shielded room to prevent the influence of electromagnetic jamming noise from the outside.

[0071] Hereinafter, the method for producing a laminate sheet of the present invention will be described with reference to specific examples, but the present invention is not limited to the following embodiments.

[0072] First, a laminated sheet in which rubber or a thermoplastic elastomer is used as a base polymer of a substrate will be described as an example. First, a predetermined amount of desired particles X is mixed into the base polymer, and the particles are mixed and mixed with a known device such as a kneader, a Banbury mixer, a mill mixer, a roll mill, a jet mill, or a ball mill to obtain a particle-containing base polymer mixture. The base polymer alone or the prepared particle-containing base polymer is rolled or melt extruded by a batch press to form a sheet of a desired thickness. Then, a sheet corresponding to the prepared layer A and a sheet corresponding to layer B containing more particles X than the prepared layer A are alternately stacked in a total of 5 layers or more, and pressed or laminated to obtain a laminated sheet. The fusion temperature at this time depends on the type of resin used, but is preferably 150°C to 400°C, more preferably 250°C to 380°C.

[0073] Next, a manufacturing method of a laminated sheet in which a thermoplastic resin exhibiting flexibility, which is a preferred resin in the present invention, is used, in which only the B layer contains particles X, and neither the A layer nor the B layer contains particles Y, will be described as an example. First, the thermoplastic resin prepared in the form of pellets and a predetermined amount of particles X are kneaded in a twin-screw extruder and extruded into a gut shape, which is cooled in a water tank and cut with a chip cutter to form a master pellet containing particles X. At this time, the particles X may be dry-blended with the resin and then metered and fed from a hopper, or side-fed into the molten resin from an arbitrary position of the extruder using a side feeder. The feeding method is not limited to the above, and can be appropriately selected according to the specific gravity and shape of the particles used.

[0074] The thermoplastic resin compositions constituting the layers A and B are then dried in hot air or under vacuum, and fed to separate extruders, where they are heated and melted to a temperature equal to or higher than the melting point of the thermoplastic resin. The extrusion rate is then made uniform using a gear pump or the like, and the thermoplastic resin composition is discharged, and foreign matter, modified thermoplastic resin, and the like are removed using a filter or the like.

[0075] Next, these thermoplastic resin compositions are laminated in a multi-layer lamination device capable of laminating the desired number of layers, molded into a desired shape with a die, and discharged into a sheet. The sheet-like material discharged from the die is extruded onto a cooling body such as a casting drum, and cooled and solidified to become a cast sheet. At this time, since the cast sheet itself exhibits electrical conductivity, it is preferable to use a method in which air is blown out from a slit-shaped, spot-shaped, or planar device to bring the cast sheet into contact with a cooling body such as a casting drum and rapidly solidify it, or a method in which the cast sheet is brought into contact with a cooling body with a nip roll and rapidly solidify it.

[0076] As the multi-layer lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but in particular, in order to efficiently obtain the multi-layer laminate of the present invention, it is preferable to use a feed block having a fine slit. When such a feed block is used, the device does not become extremely large, so that the amount of foreign matter generated due to thermal deterioration is small, and high-precision lamination is possible even when the number of layers is extremely large. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. Furthermore, this device has the advantages that the thickness of each layer can be adjusted by the shape (length, width) of the slit, making it easy to achieve any layer thickness, and that the effect of the resin flow during the lamination process makes it easy to orient the particles in the direction of the laminated sheet surface.

[0077] When a laminate sheet is produced using a slit-type feedblock, the thickness and distribution of each layer can be adjusted by adjusting the pressure balance by changing the length and width of the slit. The length of the slit refers to the length of the comb teeth that form the flow path for alternately flowing layers A and B inside the slit plate. In addition, a method of forming a laminate in the feedblock and then stacking the layers through a static mixer to double the number of layers can also be used to increase the number of layers.

[0078] The cast sheet obtained can be biaxially stretched in the longitudinal direction and the transverse direction as necessary. When biaxial stretching is performed, the stretching may be performed sequentially or simultaneously. In addition, re-stretching may be performed in the longitudinal direction and / or the transverse direction as necessary.

[0079] First, sequential biaxial stretching in which the sheet is stretched in the longitudinal direction and then in the transverse direction will be described. Here, stretching in the longitudinal direction refers to uniaxial stretching for giving the sheet a molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage, or in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 7.0 times, and particularly preferably 1.5 to 4.0 times. In addition, the stretching temperature is preferably set within the range of the glass transition temperature of the resin constituting the sheet to the glass transition temperature + 100°C and below the melting point of the resin. The uniaxially stretched laminated sheet thus obtained can be subjected to surface treatment such as corona treatment, frame treatment, and plasma treatment as necessary, and then a primer layer can be formed to improve adhesion with the film to be laminated on the upper side. In the in-line coating process, the primer layer may be applied to one side, or to both sides simultaneously or one side at a time.

[0080] The stretching in the width direction means stretching for giving a width direction orientation to the sheet, and is usually performed by conveying the sheet while holding both ends with clips using a tenter. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 7.0 times, and particularly preferably 1.5 to 5.0 times. The stretching temperature is preferably the glass transition temperature of the resin constituting the sheet to the glass transition temperature + 120°C. The laminated sheet thus biaxially stretched is subjected to a heat treatment in the tenter at a temperature higher than the stretching temperature and lower than the melting point, and is uniformly cooled slowly, cooled to room temperature, and wound up. In addition, when the heat treatment is followed by the cooling slowly, a relaxation treatment or the like may be performed in the longitudinal direction and / or the width direction in order to give a low orientation angle and thermal dimensional stability to the sheet, if necessary.

[0081] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the obtained cast sheet may be subjected to surface treatment such as corona treatment, frame treatment, plasma treatment, etc., as necessary, and then functions such as easy slip, easy adhesion, and antistatic properties may be imparted by in-line coating. In the in-line coating process, the coating layer may be applied to one side of the sheet, or may be applied to both sides simultaneously or one side at a time.

[0082] Next, the cast sheet is introduced into a simultaneous biaxial tenter, and conveyed while both ends of the sheet are held by clips, and is stretched simultaneously and / or stepwise in the longitudinal and transverse directions. The simultaneous biaxial stretching machine (tenter) may be of the pantograph type, screw type, drive motor type, linear motor type, etc., but the drive motor type or linear motor type, which can change the stretching ratio at any desired position and can perform relaxation treatment at any desired position, is preferred. The stretching ratio varies depending on the type of resin, but is usually preferably 2.0 to 50 times, and more preferably 4.0 to 20 times, in terms of area ratio. The stretching speed may be the same or different speeds in the longitudinal and transverse directions. The stretching temperature is preferably the glass transition temperature of the resin constituting the alternating laminate unit to glass transition temperature + 120°C.

[0083] The sheet thus simultaneously biaxially stretched is preferably subsequently heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. During this heat treatment, it is preferable to instantly relax the sheet in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone in order to suppress the distribution of the main orientation axis in the transverse direction. After being heat-treated in this manner, the sheet is uniformly cooled slowly, cooled to room temperature, and wound up. If necessary, the sheet may be relaxed in the longitudinal direction and / or transverse direction when being cooled slowly from the heat treatment. The sheet may also be relaxed in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone.

[0084] Furthermore, layers with different dielectric constants can be laminated on the outermost surface of the laminated sheet of the present invention for the purpose of increasing electromagnetic wave permeability or causing electromagnetic wave reflection. At this time, a coating layer containing a material exhibiting suitable electrical conductivity / magnetic properties may be applied, or different resin layers / mesh layers may be laminated via an adhesive sheet or the like. In addition, resin / metal layers can be appropriately laminated according to the required function by sputtering (such as planar or rotary magnetron sputtering), evaporation (such as electron beam evaporation), chemical vapor deposition, metalorganic chemical vapor deposition, plasma enhanced / assisted / activated chemical vapor deposition, ion sputtering, etc., which are used as sheet metal coating techniques.

[0085] Furthermore, the laminate sheet of the present invention can be combined with an electromagnetic wave reflecting layer capable of shielding a wide frequency band to provide a laminate sheet that more strongly shields only some specific frequencies. On the other hand, a new layer exhibiting a low complex dielectric constant for lowering the reflection of electromagnetic waves on the surface can be provided on the outermost surface of the laminate sheet to provide a laminate sheet with a higher electromagnetic wave absorption effect. In addition to the latter, it is also preferable that the layer exhibiting a high complex dielectric constant of the laminate sheet exhibits a layer thickness distribution in which the layer thickness decreases continuously from the surface to the inside of the sheet. Since the concentration of the electromagnetic wave suppressing material added to the layer exhibiting a high complex dielectric constant is constant in this laminate sheet, the thickness of the layer exhibiting a high complex dielectric constant is continuously reduced from the surface layer to the inner layer, so that the electromagnetic wave suppressing material is more densely connected in the inner layer, and the complex dielectric constant gradually increases. This allows the electromagnetic waves to be taken into the interior of the laminate sheet without being carelessly reflected, thereby enhancing the effect of electromagnetic wave absorption. EXAMPLES

[0086] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Each characteristic was measured by the following methods.

[0087] (Methods for measuring characteristics and evaluating effects) The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.

[0088] (1) Layer thickness, number of layers, and layer structure The layer structure of the laminate sheet was determined by observing a sample cut out of a cross section using a microtome under a transmission electron microscope (TEM). More specifically, a transmission electron microscope H-7100FA (manufactured by Hitachi, Ltd.) was used to observe the cross section of the laminate sheet at an accelerating voltage of 75 kV, and cross-sectional photographs were taken to identify the number of layers and the layer structure, and the thickness of each layer was measured using the length measurement function of the microscope. In some cases, RuO 4 Or OsO 4 The staining technique used was based on the above, and the magnification was set at 10,000 times.

[0089] (2) Transmission loss, return loss The measurement unit was changed as follows according to the measurement frequency band, and measurements were performed.

[0090] (2-1) 1GHz~40GHz frequency band The attenuation of the laminated sheet was measured using a vector network analyzer (E8361A) manufactured by Agilent Technologies. A donut-shaped coaxial waveguide with an outer diameter of φ7 mm and an inner diameter of φ3.04 mm was used for the 0.5 GHz to 18 GHz frequency band, a rectangular waveguide with a rectangular shape of 4.32 mm × 10.67 mm was used for the 18 to 26.5 GHz frequency band, and a rectangular waveguide with an internal shape of 3.56 mm × 7.11 mm was used for the 26.5 to 40 GHz frequency band. The attenuation in the MD direction was measured when the electric field direction in the waveguide and the MD direction of the laminated sheet were set parallel, and the attenuation in the TD direction was measured when the electric field direction in the waveguide and the MD direction of the laminated sheet were set parallel. The measurement interval was set so that 200 points could be measured for each frequency band. In the transmission attenuation measurement, S, which represents the intensity ratio of the transmitted electromagnetic wave to the incident electromagnetic wave, was used. 21 The maximum value of the S parameter was taken as the transmission loss. When measuring the return loss, a 3 mm aluminum metal plate was placed on the back of the laminated sheet sample, creating a state in which the incident electromagnetic wave would be totally reflected if there was no electromagnetic wave absorption by the laminated sheet. S11 The return loss peak was analyzed using the S-parameter values.

[0091] (2-2) 40~110GHz frequency band (return loss) A measurement sample was prepared by attaching an aluminum metal plate to the back of a 150 mm square laminated sheet. Using a lens antenna type oblique incidence type electromagnetic wave absorber (electromagnetic wave absorbing material) return loss measurement device LAF-26.5B manufactured by Keycom Co., Ltd., electromagnetic waves were irradiated at an oblique incidence of 15° in accordance with JIS R 1679 (2007), and the return loss was measured for each frequency band of 33 to 50 GHz (WR-22), 50 to 75 GHz (WR-15), and 75 to 110 GHz (WR-10). When the MD direction of the laminated sheet was set parallel to the electric field direction, the attenuation in the MD direction was taken, and when the TD direction was set parallel, the attenuation in the TD direction was taken. This measurement method also measures values ​​from 33 to 40 GHz, but the return loss in the frequency band from 33 GHz to less than 40 GHz was measured using the measurement data in (2-1).

[0092] (2-3) 40~110GHz frequency band (transmission attenuation) The laminated sheet was cut into a 150 mm square, and a Keycom lens antenna type oblique incidence type electromagnetic wave absorber (electromagnetic wave absorbing material) return loss measurement device LAF-26.5 was set at 180°. The laminated sheet was placed between the antennas perpendicular to the electromagnetic wave propagation direction. 21 The transmission attenuation was analyzed using the S-parameter values ​​of the above. When the electric field direction and the MD direction of the laminated sheet were placed parallel to each other, the attenuation in the MD direction was calculated, and when the electric field direction and the TD direction were placed parallel to each other, the attenuation in the TD direction was calculated.

[0093] (3) Relative permittivity (ε), relative permeability (μ) When measuring transmission attenuation, 21 Together with the S-parameter values ​​of S 11The S parameter values ​​were obtained. From the S parameter values, the relative permittivity and relative permeability were calculated using the Nicolson-Ross model using Keysight Technologies' analysis software (N1500A). The relative permittivity measured with the vibration direction of the electric field vector parallel to the MD direction of the sample was defined as MDε', MDε'', and the relative permeability was defined as MDμ', MDμ''. Similarly, the relative permittivity measured with the vibration direction of the electric field vector parallel to the TD direction of the sample was defined as TDε', TDε'', and the relative permeability was defined as TDμ', TDμ''.

[0094] (4) Uneven return loss The return loss was measured at five points at 30 cm intervals in the longitudinal direction, and the standard deviation of the measurement results was divided by the average value of the measurement results to determine the return loss unevenness, which was judged as follows: ○: Attenuation unevenness is 0 or more and less than 0.1 △: Attenuation unevenness is 0.1 or more and less than 0.3 ×: Attenuation unevenness is 0.3 or more.

[0095] (5) Volume resistivity Measurements were performed using a microresistivity meter (ADVANTEST R8340) and a test device (ADVANTEST R12702A) in accordance with JIS C 2139-3-1 (2018). The applied voltage was adjusted between 1 and 100 V according to the resistance value.

[0096] (6) Formability The laminated sheet cut into 250mm squares was heated to 90 degrees in a vacuum forming machine and a forming test was carried out. The forming mold used was a box type with a height of 1.5cm, width of 12cm, and depth of 7cm. The quality of the formed product was judged by visual observation as follows. ⊚: There was absolutely no residual air and molding was excellent. ◯: A little air remained in the corners, but the sides were able to conform, and a box-shaped molded product was obtained without any major wrinkles. △: Although the box shape was formed, air remained in the corners and the sides could not conform to the shape, or large wrinkles appeared. ×: The box shape was not obtained after the molding test, or tears occurred.

[0097] (Components used in each Example and Comparative Example) <Resin> Polyethylene terephthalate resin: Polyethylene terephthalate resin with a melting point of 254°C and a viscosity IV of 0.63 <Particle X> Carbonyl iron particles: Carbonyl iron particles with Fe content of 97%, specific gravity of 1.49 g / mL, and average particle size (D50) of 3.5 μm ε iron oxide particles: ε iron oxide particles with an average particle size of 0.1 μm and Fe:Ga:O (molar ratio) = 1.98:0.02:3.00 Spherical Sendust particles: Spherical Sendust particles with an average particle size of 0.1 μm and an aspect ratio of 1.0 Flat Sendust particles: Flat Sendust particles with an average particle size of 0.1 μm and an aspect ratio of 2.0 <Particle Y> Ketjen black particles A: Ketjen black particles with DBP oil absorption of 350 mL / 100 g and bulk density of 100 g / L · Ketjen black particles B: Ketjen black particles with DBP oil absorption of 500mL / 100g and bulk density of 150g / L.

[0098] Example 1 80 parts by mass of polyethylene terephthalate resin was mixed with 20 parts by mass of carbonyl iron particles, and master pellets A were prepared using a twin-screw kneading extruder. Polyethylene terephthalate resin was used as the resin constituting layer A, and the above master pellets A was used as the resin composition constituting layer B. The prepared polyethylene terephthalate resin and master pellets A were each fed into two twin-screw extruders in the form of pellets, and both were melted at 280°C, kneaded and extruded, joined in a feed block with 61 slits, and passed through one static mixer to form a laminated sheet with a thickness of 1 mm in which 61 layers were alternately laminated in the thickness direction, with layer A as the outermost layer, so that the thickness of each layer was uniform. The evaluation results for each item are shown in Table 1. The thickness direction refers to the direction perpendicular to the sheet surface.

[0099] (Examples 2 to 5, 11 to 13, Comparative Example 4) A laminate sheet was obtained in the same manner as in Example 1, except that the composition of each layer and the thickness of the laminate sheet were adjusted as shown in Table 1. The evaluation results of each item are shown in Table 1. The thickness of the laminate sheet was adjusted by the amount of pellets supplied during extrusion. The same applies to the following cases, except for Comparative Example 3.

[0100] Example 6 97 parts by mass of polyethylene terephthalate resin was mixed with 3 parts by mass of Ketjen black particles A, and a twin-screw kneading extruder was used to prepare master pellets B. A laminate sheet was obtained in the same manner as in Example 1, except that master pellets B were used as the resin composition constituting layer A, and the thickness of the laminate sheet was adjusted as shown in Table 1. The evaluation results for each item are shown in Table 1.

[0101] Example 7 98 parts by mass of polyethylene terephthalate resin was mixed with 2 parts by weight of Ketjen black particles B, and a twin-screw kneading extruder was used to prepare master pellets C. A laminate sheet was obtained in the same manner as in Example 1, except that master pellets C were used as the resin composition constituting layer A, and the thickness of the laminate sheet was adjusted as shown in Table 1. The evaluation results of each item are shown in Table 1.

[0102] Example 8 A laminate sheet was obtained in the same manner as in Example 3, except that a feedblock was used that exhibited a layer thickness distribution in which the thickness of layer B increased continuously from the surface layer toward the center and the layer thickness decreased continuously from the center toward the opposite surface layer, and the thickness of the laminate sheet was adjusted as shown in Table 1. The evaluation results for each item are shown in Table 1.

[0103] Example 9 A laminated sheet having a thickness of 0.5 mm was obtained in the same manner as in Example 1, except that the raw material composition of layer B was as shown in Table 1, and then this was stretched 2.5 times in the MD direction at 85° C. to obtain a laminated sheet having a thickness of 0.2 mm. The evaluation results for each item are shown in Table 1.

[0104] Example 10 A laminate sheet was obtained in the same manner as in Example 6, except that the raw material composition was as shown in Table 1. The evaluation results for each item are shown in Table 1.

[0105] Comparative Example 1 A laminate sheet was obtained in the same manner as in Example 1, except that the feed block had a two-layer structure and three layers were laminated in a static mixer. The evaluation results for each item are shown in Table 1.

[0106] Comparative Example 2 A laminate sheet was obtained in the same manner as in Example 1, except that no carbonyl iron particles were added and layer B was made of only polyethylene terephthalate. The evaluation results for each item are shown in Table 1.

[0107] Comparative Example 3 Master pellets (referred to as master pellets D to I, respectively) were prepared by adding 2 parts by mass, 4 parts by mass, 8 parts by mass, 16 parts by mass, 32 parts by mass, and 64 parts by mass of carbonyl iron particles to 100 parts by mass of polyethylene terephthalate resin, and pressed at 280°C to a thickness of 20 μm to obtain sheets D to I. Twelve sheets of the pressed sheets D, E, F, G, H, I, D, E, F, G, H, and I were stacked in this order, and further pressed at a temperature of 180°C to obtain a laminated sheet. The evaluation results of each item are shown in Table 1.

[0108] [Table 1]

[0109] In Comparative Example 3, since the sheet was press-formed, there was no longitudinal direction or width direction, and therefore an arbitrary direction parallel to the sheet surface and a direction perpendicular to the sheet surface were regarded as the longitudinal direction and width direction, respectively. [Industrial Applicability]

[0110] The laminated sheet of the present invention is made by laminating two types of layers (layer A and layer B) with different amounts of 3d transition elements, and thus can achieve high electromagnetic wave shielding properties while being easily molded and thin, which was difficult to achieve with conventional single-film or low-layer sheets. In a preferred embodiment, it can sharply and strongly shield only electromagnetic waves of a specific frequency, thereby preventing malfunctions of devices that use electromagnetic waves of a similar frequency band, and preventing information leakage in large-capacity information communication due to high-frequency electromagnetic waves. Specifically, it can be suitably used in electronic devices and communication devices that use communication technology using electromagnetic waves in the GHz frequency band, or vehicles that use them as a means of transportation, or transportation facilities including all kinds of infrastructure for traffic control. [Explanation of symbols]

[0111] 1: Incident electromagnetic wave 2: Transmitted electromagnetic waves 3: Electromagnetic shielding materials 4: Electromagnetic wave reflective layer 5: Reflected electromagnetic waves 6: Baseline 7: Return loss peak 1 8: Peak top of return loss peak 1 9: Return loss at peak top I 10: Half-value width R of return loss peak 1 11: Vibration direction of electric field vector 12: Direction of electromagnetic waves 13: Projection surface 14: The trajectory of the tip of an oscillating electric field vector

Claims

1. The present invention relates to a unit in which five or more A layers and B layers are alternately laminated, and at least one of the A layers and the B layers contains particles (particles X) containing 1 mass % or more and 100 mass % or less of a 3d transition element in an amount of 0.5 volume % or more and 90 volume % or less, and the B layer contains more particles X than the A layer, and the longitudinal dielectric constant of an arbitrary layer (α layer) located in the middle is MDE(α), the longitudinal dielectric constants of layers adjacent to the α layer are MDE(α-1) and MDE(α+1) ), where TDE(α) is the dielectric constant in the width direction of the α layer and TDE(α-1) and TDE(α+1) are the dielectric constants in the width direction of the layers adjacent to the α layer, there is one of the following: a location where MDE(α)<MDE(α-1) and MDE(α)<MDE(α+1) or a location where TDE(α)<TDE(α-1) and TDE(α)<TDE(α+1); and the relative magnetic permeability of the laminate sheet has uniaxial anisotropy.

2. A unit comprising five or more layers of A and B alternately laminated together, wherein at least one of the A and B layers contains 0.5% by volume to 90% by volume of particles (particles X) containing 1% by mass to 100% by mass of a 3d transition element, and the B layer contains more particles X than the A layer, wherein the longitudinal dielectric constant of an arbitrary intermediate layer (α layer) is MDE(α), the longitudinal dielectric constants of layers adjacent to the α layer are MDE(α-1) and MDE(α+1), a dielectric constant in the width direction of the α layer is TDE(α) and a dielectric constant in the width direction of a layer adjacent to the α layer is TDE(α-1) and TDE(α+1), respectively; either one of a portion where MDE(α)<MDE(α-1) and MDE(α)<MDE(α+1) or a portion where TDE(α)<TDE(α-1) and TDE(α)<TDE(α+1) is present; and the ratio of the major axis to the minor axis of the particle X is 1.5 or more.

3. 3. The laminate sheet according to claim 1 or 2, characterized in that it has at least one return loss peak in a frequency band of 1 MHz to 100 GHz, and when the return loss peak having the largest peak-top return loss in the frequency band is defined as return loss peak 1, the return loss of the return loss peak 1 is 5 dB or more and 150 dB or less.

4. 4. The laminate sheet according to claim 3, wherein a value obtained by multiplying the relative permeability in the longitudinal direction at the return loss peak 1 by the concentration (volume %) of the particles X in the B layer, and a value obtained by multiplying the relative permeability in the width direction at the return loss peak 1 by the concentration (volume %) of the particles X in the B layer are both 0.5 or more and 1000 or less.

5. A laminate sheet as described in claim 3 or 4, characterized in that when the real part and imaginary part of the longitudinal dielectric constant at the return loss peak 1 are MDε' and MDε'', respectively, and the real part and imaginary part of the widthwise dielectric constant at the return loss peak 1 are TDε' and TDε'', respectively, MDε' / MDε'' and TDε' / TDε'' are both 1 or more and 1000 or less.

6. 6. The laminate sheet according to claim 1, wherein at least one of the layers containing the particles X has a thickness of 1 nm or more and 30 μm or less.

7. 7. The laminate sheet according to claim 1, wherein the thickness of said layer B increases continuously from at least one surface layer to a layer at the center of the sheet.

8. 8. A laminate sheet according to claim 1, characterized in that when particles Y are particles containing 10% by mass or more and 100% by mass or less of at least one element selected from C, Ag, and Au and having a content of 3d transition elements of less than 1% by mass, at least one of the A layer and the B layer contains 0.5% by volume or more and 90% by volume or less of the particles Y.

9. 9. The laminate sheet according to claim 1, wherein the logarithm of Ω to the base 10 of the volume resistivity of the laminate sheet is 2 or more and 16 or less.

10. 10. The laminate sheet according to claim 1, wherein the average particle size of the particles X is 0.01 μm or more and 10 μm or less.

11. 2. The laminate sheet according to claim 1, wherein the ratio of the major axis to the minor axis of said particles X is 1.5 or more.

12. The laminate sheet according to any one of claims 2 to 11, characterized in that, when the particle X is cut along a plane perpendicular to the major axis and including the minor axis, a cross section of the particle X is surrounded by a rectangle having a minimum area, and the ratio of the length of the short side to the length of the long side of the rectangle is 0.5 or more and 1.0 or less.

13. 13. The laminate sheet according to claim 1, having an adhesive layer having a thickness of 1 μm or more and 10 mm or less on at least one surface.

14. 14. An electromagnetic wave-related product comprising an electrical product, a communication device, or a means of transportation, the laminate sheet according to claim 1 being mounted on the electromagnetic wave-related product.

Citation Information

Patent Citations

  • Electromagnetic interference suppressor

    JP1998106821A

  • Composite magnetic body and manufacture thereof

    JP2000243615A

  • Electromagnetic-wave-disturbance preventive material

    JP2000244167A

  • Electromagnetic wave absorbing radiating sheet

    JP2002076683A

  • Electromagnetic wave absorption sheet and its manufacturing metod

    JP2004039703A